Contribution of Cereal-Legume Association to the Yield and Grain Quality of Cereals (Biological Sciences - PJSIR, 2006)
A study on the mixed cereal-legume cultivation in different planting patterns was undertaken for two consecutive years. The aim was to investigate the contribution of the association of legumes towards yield and grain quality of cereal crops. The data indicated that the association of legumes in different planting pattern with sorghum affected the yield and grain quality of sorghum. During both the years of study, the double row strips (30/90 cm) planting pattern significantly increased the grain yield of sorghum, as compered with single rows (60 cm apart) and triple row strips (30/120 cm). The grain yield of sorghum decreased when sorghum was associated with mungbean or guar, but the additional harvest of intercrops increased the total productivity. The difference in grain yield between the treatment means of interaction was non-significant. Moreover, in the first year of study, protein content of sorghum grain was not significantly affected by the planting pattern, but in the second year of study, double and triple row strips planting pattern significantly increased the grain protein content (respectively, 9.41% and 9.34% ) of sorghum, as compared with single row planting pattern (protein content of 9.19%). Sorghum grain protein content of 9.51 and 9.49% produced in association with mungbean was signifi- cantly more than the grain protein content of sorghum alone or sorghum grown in the association with guar during 1999 and 2000, respectively. Increase in grain protein content of sorghum, when associated with mungbean, was attributed to the N transfer from companion mungbean to sorghum. It may be concluded from the results obtained that sorghum + mungbean association in the double row strips (30/90 cm) planting pattern can efficiently utilize the available resources to improve the grain quality and overall production of sorghum-based cropping system.